Quality evaluation of Tetrastigma hemsleyanum different parts based on quantitative analysis of 42 bioactive constituents combined with multivariate statistical analysis. Issue 5 (5th April 2022) - Luo, Yiyuan; Yang, Yingxin; Yang, Xinyu; Sun, Chonglu; Chen, Hongjiang
Abstract: Introduction: The root of Tetrastigma hemsleyanum (RTH) has been widely used as a folk medicine in China. Meanwhile, its stems (STH) and leaves (LTH) are consumed as functional tea and food supplementation. Therefore, it is important to get a better understanding of the distribution of bioactive constituents in different parts of T. hemsleyanum . Objective: To develop a method for quantitative analysis of multiple bioactive constituents and comparing their distribution in RTH, STH and LTH. Methods: Ultra‐performance liquid chromatography triple quadrupole ion trap tandem mass spectrometry (UPLC‐QTRAP‐MS/MS) was used for the quantitative analysis. The quantitative data were further analysed by principal component analysis (PCA), hierarchical cluster analysis (HCA) and partial least squares determinant analysis (PLS‐DA). Results: Forty‐two constituents in RTH, STH and LTH, including 14 flavonoids, three phenolic acids, 15 amino acids and 10 nucleosides, were quantitatively determined. The contents of flavonoids and phenolic acids in LTH were significantly higher than those in RTH and STH. While the contents of amino acids and nucleosides in LTH were less than those in RTH and STH. Multivariate statistical analysis can significantly classify and distinguish RTH, STH, and LTH. Conclusions: The present method would be helpful for the quality control of T. hemsleyanum, and the results would be useful for the efficient utilisation of T. hemsleyanum in the future. Abstract : 42 constituents, including 14 flavonoids, 3 phenolic acids, 15 amino acids and 10 nucleosides, were quantitatively determined by using UPLC‐QTRAP‐MS/MS in the roots (RTH), stems (STH) and leaves (LTH) of Tetrastigma hemsleyanum. The contents of flavonoids and phenolic acids in LTH were significantly higher than those in RTH and STH, while the contents of amino acids and nucleosides in LTH were less than those in RTH and STH. Multivariate statistical analysis can significantly classify and distinguish RTH, STH, and LTH.